EVALUATION OF THE IMPLEMENTATION AND EFFECTIVENESS OF GOOD CORPORATE GOVERNANCE IN STATE-OWNED ENTERPRISES: A CASE STUDY OF PELINDO AS A RECIPIENT OF THE 'INDONESIA TRUSTED COMPANIES 2024' AWARD (Musytari : Jurnal Manajemen, Akuntansi, dan Ekonomi, 2025)
Abstract          This study explores how the implementation of Good Corporate Governance (GCG) contributes to both financial performance and corporate reputation in Indonesia’s state-owned enterprise (SOE) landscape. Focusing on PT Pelabuhan Indonesia (Pelindo)—a key national port operator and recipient of the "Indonesia Trusted Companies 2024" award—this research adopts a document-based case study approach. By systematically analyzing a variety of official records, including audited financial statements, annual reports, GCG self-assessment scores, operational performance summaries, and sustainability disclosures, the study aims to evaluate the real impact of GCG practices without relying on interviews or perception-based data. The analysis builds upon the conceptual framework of Putri and Meutia (2024), which links the quality of internal controls, the role of internal audits, and governance structures to key performance outcomes. In Pelindo’s case, these governance mechanisms have not only ensured compliance with state regulations and international best practices but have also translated into tangible improvements in financial indicators such as Return on Equity (ROE), Operating Profit Margin (OPM), and asset turnover ratios over the 2022–2024 period. Moreover, Pelindo's high GCG assessment scores and its consistent ESG (Environmental, Social, and Governance) disclosures appear to have strengthened stakeholder confidence and enhanced the company's corporate image, ultimately contributing to its national recognition as a trusted SOE. What sets this study apart is its methodological rigor in triangulating secondary data sources to draw robust inferences about governance effectiveness. By relying entirely on verifiable documentation—rather than interviews or subjective assessments—the research presents a replicable and audit-proof model for evaluating GCG in other state-owned enterprises. Furthermore, this approach offers critical insights into how public recognition, such as GCG awards, often reflects deeper institutional practices and performance trends, rather than being symbolic or ceremonial in nature. The study underscores the strategic importance of GCG in shaping both short-term operational outcomes and long-term reputational capital. It argues that transparent, accountable, and sustainability-oriented governance is not merely a regulatory obligation but a value-creating asset for SOEs, especially in complex institutional environments like Indonesia. The findings are expected to benefit corporate leaders, regulators, and policymakers seeking to enhance GCG frameworks across the public sector. In doing so, the research also contributes to the broader academic discourse on governance in emerging markets, where the convergence of state ownership and private sector efficiency continues to present both challenges and opportunities.Keywords: Good Corporate Governance, State-Owned Enterprises, Pelindo, Corporate Performance, Governance Assessment, ESG Reporting, Reputation, Document-Based Case Study, Public Sector Reform.